Helicascus alatus (Morosphaeriaceae), a new freshwater species from southwestern China - Zeng, Ming; Huang, Shi-Ke; Hyde, Kevin D.; Zhao, Qi (Phytotaxa, 2018)
Helicascus alatus sp. nov., is described from submerged wood collected in a river in southwestern China. It is characterized by the unilocular ascomata, bitunicate, pedicellate asci and guttulate ascospores surrounded by wing-like sheath. Molecular phylogenetic analyses based on combined LSU, ITS, SSU (r) DNA and TEF1-α sequences data place this species in Morosphaeriaceae (Pleosporales). A description, illustration, phylogenetic placement and comparison with allied taxa for the new taxon are provided.